Extended exergy analysis (EAA) of two canola farming systems in Khorramabad, Iran. (April 2020) - Amiri, Zahra; Asgharipour, Mohammad Reza; Campbell, Daniel E.; Armin, Mohammad
Abstract: Extended exergy analysis ( EEA ) is a novel method in evaluation of agricultural ecosystems. In this study, a comprehensive analysis of the sustainability of an agricultural system was carried out using this method. Specifically, we looked for sustainable patterns of canola production by performing EEAs of two canola production systems, commercial and traditional, located in Khorramabd, Iran using data from the 2017–2018 crop year. The EEA of these two systems showed that the exergy of the environmental remediation cost ( EE E ) for the traditional system was less than that of the commercial system by 2.69 × 10 4  MJ ha −1 . Accordingly, the ecological sustainability of the traditional system was found to be two times higher than the commercial system. In contrast, the values of thermodynamic indicators such as the capital conversion factor of the annual monetary value of product sales ( K cap EEA ), the extended exergy efficiency ( Ŋ EEA ), and the cumulative degree of perfection ( CDP ), respectively, indicate the higher economic value, the higher thermodynamic efficiency, and the greater optimality of the commercial system compared to the traditional system. The high consumption of inputs led to increased cumulative exergy consumption ( CExC ) in the traditional system. The high amount of CExC in the traditional system caused its thermodynamic indices to decrease. On the other hand, the high consumption of resources such as chemical fertilizers caused the EE E of the commercial system to increase. Therefore, based on the results of the EEAs performed in this study, we recommend designing new patterns for managing agricultural production systems, whereby through choosing the appropriate type and amount of inputs for each production system and by employing the required knowledge and technology for optimum production, the costs of environmental remediation will be reduced, and the thermodynamic-economic indexes will be improved. Highlights: Life cycle assessment of the inputs is important to design a sustainable production pattern. Thermodynamic indices have been used as a tool for assessing sustainability in agroecosystems. There is a direct correlation between the renewability of inputs and ecological sustainability. Management practices based on EEA lead to greater efficiency and sustainability of production systems.